The Effectiveness of Cognitive Restructuring Counselling Containing Wahdatul Ulum Values to Increase Student Perseverance - Arsini, Yenti; Wirtati, Ira; Damanik, Emeliya Sukma Dara (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
In the modern era of academic pressure, individuals often face psychological challenges that affect their ability to persevere and succeed. Cognitive restructuring counselling has been shown to be effective in changing an individual's mindset, but there have not been many studies examining the influence of the integration of spiritual values such as Wahdatul Ulum in this context. This study aims to explore the effect of integrating Wahdatul Ulum values in cognitive restructuring counseling to increase mental resilience and student perseverance. This study uses a Research and Development (R&D) approach to develop and test a cognitive restructuring counseling model that integrates the values of Wahdatul Ulum. The population is students of FITK UIN SU Medan class of 2020 totaling 195 students. The research sample was 32 BKPI students who were selected purposively. Instrument development by identifying and analyzing literature, expert validation, limited trials, and developing cognitive restructuring counselling models covering aspects of Wahdatul Ulum values. Data analysis used the Wilcoxon test that utilizes SPSS 25 to detect any significant changes. The results showed that the perseverance of the treatment group increased significantly, while the perseverance of the control group decreased. These findings support the idea that the integration of spiritual values in counselling can provide an effective holistic approach to improving individual resilience. This research provides insight into how cognitive restructuring counselling with the Wahdatul Ulum approach can help students overcome psychological barriers and improve their ability to face challenges in daily life. The practical implication is that cognitive restructuring counselling with spiritual values can be an effective alternative to guidance and counselling services to improve students' perseverance and mental resilience.